Analysis of Approaches and Teaching Tools in Maritime Educational Institutions Abroad - Voloshynov, Serhii (Pedagogical Discourse, 2019)
The article analyzes the current state of maritime education abroad. The study on the training of maritime specialists abroad is analyzed and the conclusion is made that the issue of research on approaches and means of training in maritime educational institutions abroad, aimed at improving the efficiency of maritime education, is not adequately covered. The importance of such international institutes as the International Association of Maritime Universities and the International Maritime University in improving the professional training of future maritime professionals is highlighted. It is revealed that the International Association of Maritime Universities is paying attention to the problems of the impact of virtual reality on maritime education and training, including the coverage of how to apply virtual reality in the training of maritime professionals. It is determined that the main content of the educational programs of the International Maritime University is the educational and research problems. Studies on the challenges of improving the training of maritime professionals in developing countries (South Africa, Vietnam) are analyzed. Some recommendations that may be appropriate for introducing Ukraine’s maritime education as a country undergoing a process of reforming the national education system are presented. Methods such as analysis, synthesis, comparison, generalization were used to achieve the goal. It has been established that the emphasis is on developing the digital skills of future maritime professionals and implementing the requirements of the 4th Industrial Revolution into maritime education and training. It is determined that to improve the professional training of future maritime specialists in Ukraine such approaches as interdisciplinary, dual, informative, research, integrative, as well as the principle of mobility can be used. As the result, virtual and augmented reality, mobile technologies and distance learning are identified as effective learning tools.